Implementasi Program Pelayanan Kesehatan Gratis Di Kabupaten Bintan - Calvin Antony; Novi Winarti; Rizky Octa Putri Charin (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to analyze the implementation of the Free Health Service Program in Bintan Regency. The program provides free healthcare services for residents, particularly those not registered with BPJS Kesehatan, using their Identity Card (KTP) and Family Card (KK). The study was motivated by implementation challenges, including alleged unauthorized charges and inconsistent service procedures at several healthcare facilities. A descriptive qualitative approach was employed. Primary data were collected through interviews and observations involving the Bintan Regency Health Office, Bintan Regional General Hospital (RSUD), Kijang Community Health Center (Puskesmas), and program beneficiaries, while secondary data were obtained from regulations and supporting documents. Data were analyzed using George C. Edward III’s policy implementation framework, consisting of communication, resources, disposition, and bureaucratic structure. The findings show that the program has generally been implemented effectively, supported by coordination, adequate resources, committed implementers, and clear procedures. However, limitations in health services, shortages of medical personnel, and limited public understanding remain challenges requiring continuous improvement.